Advantages and limitations for users of double pit pour-flush latrines: a qualitative study in rural Bangladesh - Faruqe Hussain; Thomas Clasen; Shahinoor Akter; Victoria Bawel; Stephen P. Luby; Elli Leontsini; Leanne Unicomb; Milan Kanti Barua; Brittany Thomas; Peter J. Winch (BMC, 2017)
Abstract Background In rural Bangladesh, India and elsewhere, pour-flush pit latrines are the most common sanitation system. When a single pit latrine becomes full, users must empty it themselves and risk exposure to fresh feces, pay an emptying service to remove pit contents or build a new latrine. Double pit pour-flush latrines may serve as a long-term sanitation option including high water table areas because the pits do not need to be emptied immediately and the excreta decomposes into reusable soil. Methods Double pit pour-flush latrines were implemented in rural Bangladesh for 'hardcore poor' households by a national NGO, BRAC. We conducted interviews, focus groups, and spot checks in two low-income, rural areas of Bangladesh to explore the advantages and limitations of using double pit latrines compared to single pit latrines. Results The rural households accepted the double pit pour-flush latrine model and considered it feasible to use and maintain. This latrine design increased accessibility of a sanitation facility for these low-income residents and provided privacy, convenience and comfort, compared to open defecation. Although a double pit latrine is more costly and requires more space than a single pit latrine the households perceived this sanitation system to save resources, because households did not need to hire service workers to empty pits or remove decomposed contents themselves. In addition, the excreta decomposition process produced a reusable soil product that some households used in homestead gardening. The durability of the latrine superstructures was a problem, as most of the bamboo-pole superstructure broke after 6-18 months of use. Conclusions Double pit pour-flush latrines are a long-term improved sanitation option that offers users several important advantages over single pit pour-flush latrines like in rural Bangladesh which can also be used in areas with high water table. Further research can provide an understanding of the comparative health impacts and effectiveness of the model in preventing human excreta from entering the environment.